2017
DOI: 10.1108/ijmce-07-2016-0057
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing instructional leadership through collaborative coaching: a multi-case study

Abstract: Purpose Executive coaching has become increasingly important for enhancing organizational leaders’ professional effectiveness. The purpose of this paper is to contribute to a growing body of research literature that examines how coaching techniques help school principals improve their instructional leadership. Design/methodology/approach Using a protocol based on a theories of practice framework (Argyris and Schön, 1974) to support principals in deepening their self-reflection, this study added the element o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 13 publications
1
28
0
Order By: Relevance
“…Also, the results of the present study was inconsistence with (Deborah 2016; Clive 2018) who asserted that coaching skills include effectively ask probing questions that get coachee communicating and sharing truth, challenges, and fears that may be inhibiting them from succeeding and giving supportive and constructive feedback [6,7]. This was supported by (Deborah 2016; Gary, Tom & Sara 2016) who stated that coach should be energetic, optimistic, prepared, willing to commit time [7,8]. This is on the same line with (Baxter & Cynthia 2013; Hawkins 2014; Lawley & Linder 2016) who found that coach is able to accommodate different personalities and learning styles; accepts constructive criticism and doesn't take it personally [10,11,29].…”
Section: Discussionmentioning
confidence: 51%
See 4 more Smart Citations
“…Also, the results of the present study was inconsistence with (Deborah 2016; Clive 2018) who asserted that coaching skills include effectively ask probing questions that get coachee communicating and sharing truth, challenges, and fears that may be inhibiting them from succeeding and giving supportive and constructive feedback [6,7]. This was supported by (Deborah 2016; Gary, Tom & Sara 2016) who stated that coach should be energetic, optimistic, prepared, willing to commit time [7,8]. This is on the same line with (Baxter & Cynthia 2013; Hawkins 2014; Lawley & Linder 2016) who found that coach is able to accommodate different personalities and learning styles; accepts constructive criticism and doesn't take it personally [10,11,29].…”
Section: Discussionmentioning
confidence: 51%
“…Peer coaching is a confidential process through coach and coachee share their expertise and provide one another with feedback, support and assistance for the purpose of enhancing learning by refining present skills, learning new skills, and/or solving classroom/clinical area-related problems [8,16,28]. Regarding coaching skills and characteristics of good coach, the results of the present study revealed that all of the study sample was not aware of the required skills and characteristics of good coach.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations